2021
DOI: 10.3390/jcm10071366
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing Patterns of Pain Medications in Unspecific Low Back Pain in Primary Care: A Retrospective Analysis

Abstract: Acute low back pain (LBP) is one of the most prevalent diseases worldwide. Since there is evidence of excessive prescriptions of analgesics, i.e., opioids, the aim of this study was to describe the use of pain medications in patients with LBP in the Swiss primary care setting. A retrospective, observational study was performed using medical prescriptions of 180 general practitioners (GP) during years 2009–2020. Patterns of pain medications (nonsteroidal anti-inflammatory drugs (NSAIDs), paracetamol, and opioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…5,[24][25][26] In our study 34% of all patients received an opioid. Comparing this percentage of opioid use to the sparse national comparative data, 20 we found that the percentage in our study was almost twice as high. In addition, we discovered higher percentages of strong opioid use, although…”
Section: Opioid Pain Medication Therapiessupporting
confidence: 44%
See 4 more Smart Citations
“…5,[24][25][26] In our study 34% of all patients received an opioid. Comparing this percentage of opioid use to the sparse national comparative data, 20 we found that the percentage in our study was almost twice as high. In addition, we discovered higher percentages of strong opioid use, although…”
Section: Opioid Pain Medication Therapiessupporting
confidence: 44%
“…Furthermore, our prescribing patterns were similar to those reported in a recent study which analyzed pharmacological treatment patterns in LBP patients in the Swiss primary care setting but regardless of diagnostic spine imaging. 20 In accordance with the available national guidance, 19 Ibuprofen, diclofenac, and mefenamic acid were the most commonly used medications and accounted for nearly 90% of all NSAID prescriptions. Alternative NSAIDs such as COX-2 inhibitors were only marginally used.…”
Section: Non-opioid Pain Medication Therapiesmentioning
confidence: 95%
See 3 more Smart Citations